Measuring the Autonomy of Female Family Heads in Savings and Loans Activities at a Microfinance Institution - Yuliantini, Linda (Yayasan Jurnal Perempuan, 2018)
It is important to study the autonomy of women's autonomy, because it is relational, multidimensional and influences the lives of women, especially regarding actions and decision-making in all aspects of their lives. This research explores the autonomy of female household heads (PEKKA) in savings and loan activities at a microfinance institution both individually and collectively. Pekka's individual autonomy is seen in the context of power through power within, power to, and power over, while collective autonomy is in line with the power with concept offered by Linda Mayoux. This study uses a qualitative approach with a female perspective. Data collection was conducted through in-depth interviews with five subjects that were selected purposively. The results showed that participation in savings and credit activities increased the autonomy of individual female heads of household more significantly compared to collective autonomy in groups.